2011
DOI: 10.1080/01690965.2010.492642
|View full text |Cite
|
Sign up to set email alerts
|

Representational complexity and memory retrieval in language comprehension

Abstract: Mental representations formed from words or phrases may vary considerably in their feature-based complexity. Modern theories of retrieval in sentence comprehension do not indicate how this variation and the role of encoding processes should influence memory performance. Here, memory retrieval in language comprehension is shown to be influenced by a target’s representational complexity in terms of syntactic and semantic features. Three self-paced reading experiments provide evidence that reading times at retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
157
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(187 citation statements)
references
References 44 publications
18
157
5
Order By: Relevance
“…The "complexity"-induced speedup would thus be a length or, equivalently, a linear position effect. Given our initial predictions, we found no evidence that increased antecedent complexity slowed down the processing of the ellipsis, as predicted by Murphy's (1985) account, or contrariwise led to speedier processing of the ellipsis, as predicted by the account of Hofmeister (2011). Rather, the Bayes factor analysis showed that the data are largely inconsistent with the assumption that increased complexity leads to faster processing.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…The "complexity"-induced speedup would thus be a length or, equivalently, a linear position effect. Given our initial predictions, we found no evidence that increased antecedent complexity slowed down the processing of the ellipsis, as predicted by Murphy's (1985) account, or contrariwise led to speedier processing of the ellipsis, as predicted by the account of Hofmeister (2011). Rather, the Bayes factor analysis showed that the data are largely inconsistent with the assumption that increased complexity leads to faster processing.…”
Section: Discussioncontrasting
confidence: 50%
“…Assuming that retrieval takes place in both the ellipsis and control conditions, the observed processing pattern would be more in line with the reasoning of Murphy (1985), where it takes more time to copy more information from the antecedent, than with that of Hofmeister (2011), where elaboration should lead to facilitation. Indeed, our analyses showed more evidence for the former view than the latter.…”
Section: A More Precise Notion Of Complexity-based Facilitation Is Nementioning
confidence: 65%
See 3 more Smart Citations